Streptococcus pneumoniae carriage, antimicrobial resistance, and serotype distribution in children and adults from Paraguay in the post-vaccinal era - Russomando, Graciela; Fariña, Norma; Amour, Selilah; Grau, Lorena; Guillen, Rosa; Abente, Sonia; Aldama, Monserrat; Hahn, Ingrid; Castro, Hector; Messaoudi, Mélina; Sanchez, Zunilda; Picot, Valentina; et al. (Frontiers in Public Health, 2025)
IntroductionInfections due to Streptococcus pneumoniae, including pneumonia and meningitis, are a leading cause of morbidity and mortality, especially in low-and lower middle-income countries (LMICs) worldwide. Most reviews highlight the geographical differences in serotype replacement and antibiotic resistance observed through invasive pneumococcal disease (IPD) surveillance, predominantly in high-income countries; however, data from many LMICs remain limited or poorly characterized. This study was conducted among healthy children aged 2–59 months and adults living in the same household, to determine pneumococcal carriage rates, serotype distribution, and the serotypes associated with antibiotic resistance profiles, following the introduction of PCV10/PCV13.MethodsNasopharyngeal samples (NP) were obtained from 420 child/adult pairs between September 2018 and October 2019. Detection, serotyping, pneumococcal isolation and antibiotic susceptibility testing were performed using standardized protocols. Additionally, vaccine impact on serotype prevalence was assessed by comparison with a group of 100 healthy carriers under 5 years of age, recruited at the same hospital between 2010 and 2014, prior to vaccine introduction.ResultsWe observed higher pneumococcal carriage in children (39%) than in adults (20%) and limited intrafamilial transmission. Vaccine serotypes continue to circulate among children despite vaccination, accompanied by a rise in non-vaccine serotypes. Almost 11% of fully vaccinated children still carried vaccine serotypes. Antibiotic resistance to beta-lactams and macrolides has increased; nearly one-third of the isolates were multidrug resistant while multi-drug resistant pediatric isolates were predominantly associated with serotypes 19F and 19A.ConclusionOur findings reveal worrying trends in the epidemiology of S. pneumoniae in Paraguay, including the persistence of vaccine-type serotypes among vaccinated children and an increasing resistance to antibiotics of isolated strains. Given the critical role of carriage studies in monitoring the impact of PCV in LMICs, the public health community should explore ways to improve their feasibility and cost-effectiveness and better integrate these efforts into routine vaccine preventable disease surveillance systems.